2017
DOI: 10.1074/jbc.m117.806000
|View full text |Cite
|
Sign up to set email alerts
|

CDK9 and SPT5 proteins are specifically required for expression of herpes simplex virus 1 replication-dependent late genes

Abstract: DNA replication greatly enhances expression of the herpes simplex virus 1 (HSV-1) γ2 late genes by still unknown mechanisms. Here, we demonstrate that 5,6-dichloro-1-β-d-ribofuranosylbenzimidazole (DRB), an inhibitor of CDK9, suppresses expression of γ2 late genes with an IC50 of 5 μm, which is at least 10 times lower than the IC50 value required for inhibition of expression of early genes. The effect of DRB could not be explained by inhibition of DNA replication per se or loading of RNA polymerase II to late … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Conversely, we have demonstrated that FIT-039 shows selective inhibition of CDK9 by targeting the ATP-binding pocket, achieving antiviral activity against multiple viruses without major toxicity to host cells (17)(18)(19). These data indicate that, as seen for HPV (26)(27)(28), the P-TEFb complex (CDK9 and cyclin T) plays a major role in viral promoter activity in multiple viral species (39)(40)(41)(42)(43)(44)(45). The ability of FIT-039 to target viral promoter activities prompted us to test its effect on a tumor virus, in which expression of specific viral genes per se is an inducer of transformation and/or malignant progression (19).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Conversely, we have demonstrated that FIT-039 shows selective inhibition of CDK9 by targeting the ATP-binding pocket, achieving antiviral activity against multiple viruses without major toxicity to host cells (17)(18)(19). These data indicate that, as seen for HPV (26)(27)(28), the P-TEFb complex (CDK9 and cyclin T) plays a major role in viral promoter activity in multiple viral species (39)(40)(41)(42)(43)(44)(45). The ability of FIT-039 to target viral promoter activities prompted us to test its effect on a tumor virus, in which expression of specific viral genes per se is an inducer of transformation and/or malignant progression (19).…”
Section: Discussionmentioning
confidence: 80%
“…Past studies indicated CDK9, over the other CDKs, is prone to be recruited to viral promoters, in association and/or cooperation with viral proteins (39-45), which we consider the mechanical background of the common antiviral effect of FIT-039. For instance, ICP22 of human simplex herpesvirus (HSV) forms complex with CDK9 and SPT5 to activate HSV-1 late gene promoter (40,41), as well as upregulating other HSV-1 transcripts (42). Regarding EB virus (EBV), P-TEFb is required for EBNA2-dependent transcripts, and CDK9 inhibition by 5, 6-dichloro-1-beta-D-ribofuranosylbenzimidazole has been previously reported to suppress those transcripts (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…The HSV-1 gB gene copy number was clearly reduced as shown by qPCR, suggesting that the HCFC1R1 deficiency affects HSV-1 propagation (Figure 6A). To further ask if loss of HCFC1R1 was correlated with the life cycle of HSV-1, we analyzed the mRNA expression of several viral genes including ICP0 (representing immediate early gene), TK (early gene), and GD (late gene) in the control and BGC-823 HCFC1R1−/− cells by qRT-PCR in 24, 48, and 72 hours after infection (2527). qRT-PCR data showed that missing HCFC1R1 significantly inhibited the mRNA transcription in BGC-823 HCFC1R1−/− cells at the various time points (Figure 6B, C, D).…”
Section: Resultsmentioning
confidence: 99%
“…Cyclin T1 (CCNT1) is a regulatory subunit of the CDK9/cyclin-T1 cyclin-dependent kinase complex, which promotes transcription via phosphorylation of RNA polymera-se II [64]. This complex is a target of many anti-cancer drugs [65][66][67] and is important for anti-viral therapy as well [68][69][70].…”
Section: Resultsmentioning
confidence: 99%